Introduction to the Special Subsection: Contemplating the BICS Essay Contest on Postmortem Survival - Houran, James (Journal of Scientific Exploration, 2022)
Well-known aerospace entrepreneur Robert T. Bigelow has contributed a great deal privately and publicly to science and technology over the years, including the realm of anomalistics and edge science [see: Kelleher, C. A., & Knapp, G. (2005). Hunt for the skinwalker: Science confronts the unexplained at a remote ranch in Utah. Paraview Pocket Books]. This generous support should be celebrated, as it is virtually unique in modern times where academic freedom and consequential funding are sparse in the controversial fields that JSE routinely spotlights. In fact, Bigelow recently formed the Bigelow Institute of Consciousness Studies (BICS) to support research on the ostensible survival of human consciousness after physical death and the potential nature of such a state. BICS therefore comprises an ongoing platform for exploration and education versus a singular act of support from a lone patron. Among the organization’s first initiatives was a global campaign to solicit the best evidence supporting the notion of postmortem survival. This venture paralleled successful ‘crowdsourcing contests’ that some companies use to drive product improvements or innovations via public competitions with cash awards [see: Segev, E. (2020). Crowdsourcing contests. European Journal of Operational Research, 281, 241–255. https://doi.org/10.1016/j.ejor.2019.02.057 ].